2013
DOI: 10.1371/journal.pone.0074406
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Alcohol Dependence Disorder among TB and HIV Infected Patients in Zambia

Abstract: ObjectivesTo determine the prevalence and correlates of alcohol dependence disorders in persons receiving treatment for HIV and Tuberculosis (TB) at 16 Primary Health Care centres (PHC) across Zambia.Methods649 adult patients receiving treatment for HIV and/or TB at PHCs in Zambia (363 males, 286 females) were recruited between 1st December 2009 and 31st January 2010. Data on socio-demographic variables, clinical disease features (TB and HIV), and psychopathological status were collected. The Mini Internationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 49 publications
7
51
1
Order By: Relevance
“…This observation is consistent with other literature from the region, 14,25 which suggests an ongoing need for outreach to men. There was also substantial evidence that measures of stigma related to both TB and HIV were correlated with hazardous/harmful alcohol use.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is consistent with other literature from the region, 14,25 which suggests an ongoing need for outreach to men. There was also substantial evidence that measures of stigma related to both TB and HIV were correlated with hazardous/harmful alcohol use.…”
Section: Discussionsupporting
confidence: 92%
“…We found a high prevalence of both, a result that is consistent with the limited literature on mental health among individuals with HIV and TB in sub-Saharan Africa. 11,2527 Depressive symptoms and hazardous/harmful alcohol use appeared to primarily affect distinct groups. Due to the small sample size, we did not formally explore correlates, but individuals who reported both were predominantly men who endorsed higher external stigma about HIV.…”
Section: Discussionmentioning
confidence: 98%
“…This is consistent with study finding in Jimma, Zambia and Vietnam which shows male predominance in Khat, Alcohol and Cigarettes smoking [18,26,30]. This could be due to due to social and biological factors or gender difference.…”
Section: Discussionsupporting
confidence: 92%
“…Various studies done across the world and India have also shown that use of alcohol increases the risk of Tuberculosis [23] [24]. In addition, both alcohol consumption and HIV infection impairs the host's defense mechanism against Tuberculosis infection and disease [25] [26]. Further, alcohol consumption also affects the adherence to HIV and Tuberculosis treatment.…”
Section: Discussionmentioning
confidence: 99%